COMPARISON OF ANTI-INFLAMMATORY ACTIVITY OF NIGELLA SATIVA AND DICLOFENAC SODIUM IN ALBINO RATS - Bashir, Muhammad Usman; Qureshi, Hamid Javaid; Saleem, Tahira (Journal of Ayub Medical College Abbottabad, 2015)
Background: Nigella sativa or Kalonji is a naturally occurring plant in Pakistan and other countries which possesses a wide range of medicinal properties, the anti-inflammatory property being one of these. Diclofenac sodium is a commonly used anti-inflammatory drug. The purpose of this study was to compare the anti-inflammatory effect of ethanolic extract of Nigella sativa seeds with that of diclofenac sodium in albino rats. Methods: This laboratory randomized controlled trial (RCT) was conducted in the Physiology Department, Services Institute of Medical Sciences (SIMS), Lahore. The study was carried out on 90 male albino rats.Five percent formalin in a dose of 50 µl was injected into sub-plantar surface of right hind paw of each rat to produce inflammation. The rats were randomly divided into three groups of thirty each. Group A was given normal saline (control); group B was given Nigella sativa seed extract; and group C received diclofenac sodium, as a reference drug. Increase in paw diameter, and total and differential leukocyte counts were measured as markers of inflammation. Results: Nigella sativa seeds extract caused significant (p<0.05) reduction in the paw inflammatory response in albino rats. The effect was longer in duration than the effect caused by diclofenac sodium; however, the extract was comparatively less potent than diclofenac sodium. The extract had no significant effect (p>0.05) on the total or differential leukocyte counts. Conclusion: Our results suggest that ethanolic extract of Nigella sativa seeds possesses potent anti-inflammatory effect in albino rats however, this effect is comparatively less but prolonged than that produced by diclofenac sodium.